Willingness to pay for improved water service: evidence from urban Peru - Galarza, Francisco (2022)
We study the willingness to pay (WTP) for a large set of improvements in water service related to water quality, continuity, and securing access for people with no house piped water during the COVID-19 pandemic. Using data from urban Peru, and the contingent valuation method, we estimate a mean WTP of around PEN 4.3 (USD 1.05), 3.7 and 1.8, respectively, for the aforementioned sets of improvements, with the combined WTP representing a 23% increase in the households’ water service monthly bill. We find that the WTP for all sets of improvements is influenced by the expenditure in bottled water (which acts as a substitute for tap water) and a proxy variable for household assets. The influence of the individual characteristics typically scrutinized by the literature (e.g. sex, age, and education) varies with the type of improvement examined. We find a significant heterogeneity in WTP across providers and calculate the users’ contribution to a water fund that could crowd-in the public investment in water infrastructure.